Human rights in the Anthropocene epoch and philosophy - Minich, Dobrochna; Karp, Janusz (Ius Novum, 2025)
The subject of this article is the issue of human and civil rights in the context of the Anthropocene. This is a multi-faceted, complex, and highly relevant issue. The origins of human rights date back to Antiquity and the natural law concept, flourishing during the Enlightenment. Nowadays, human rights have evolved into a generational framework. The advent of the Anthropocene epoch (referred to as the human epoch) has made mankind aware of its domination over nature. Human activity has led to unprecedented threats and the degradation of the natural environment, which is the material foundation of human existence. In order to mitigate the effects of the ecological crisis, it is proposed to adopt a different way of thinking – an alternative human attitude shifting from anthropocentrism to antianthropocentrism. The classic concept of the ‘common good’ has been revisited. Planet Earth is the common good of all of us and embodies the highest good for the individuals who constitute the political community. Human rights should provide the legal framework for environmental law, including climate law.